Acid and gastrin responses during intragastric titration in normal subjects and duodenal ulcer patients with G-cell hyperfunction. Issue 3 (March 1985) - Cooper, R G; Dockray, G J; Calam, J; Walker, R
Abstract : Amino acid induced acid and gastrin responses during intragastric titration at pH 2.5 and 5.5 were compared in normal subjects and duodenal ulcer patients with G-cell hyperfunction. The latter were identified on the basis of raised basal or maximal acid outputs and increased gastrin responses to feeding. In normal subjects the mixed amino acid meal stimulated only modest increases in serum gastrin, and the highest observed increase was about 30% that after a standard meal. In contrast, in the G-cell hyperfunction group the highest gastrin concentrations were similar to those after a standard meal. In the G-cell hyperfunction group the increment in serum gastrin at pH 2.5 expressed as a proportion of that at pH 5.5 was 0.29 indicating that the capacity of acid to inhibit gastrin release was well established in these patients. Acid secretory rates were close to maximal at both pH 2.5 and 5.5 during intragastric titration in the ulcer patients, but in normal subjects acid output was about 50% maximal at 2.5 and close to maximal at 5.5. The results suggest that the enhanced gastrin response to feeding in G-cell hyperfunction patients is because of increased sensitivity to amino acid stimulation rather than to diminished acid-inhibitory mechanisms.